Disruptive innovation. Hope for future education - Pilonieta, Germán (Instituto para la Investigación Educativa y el Desarrollo Pedagógico, IDEP, 2017)
In the present text I will try to enter into the very entrails of education as it is known, approaching the perspective that makes us think that it must be managed in this way, which will happen for at least many more years, To expose some alternatives that allow to visualize viable possibilities of transformation, finding other looks and dimensions to contemplate the phenomenon; Finally, a review will be made of the disruptive innovations in education, ending with an approximation to what could be a good disruptive innovation.